2017
DOI: 10.1371/journal.pone.0186487
|View full text |Cite
|
Sign up to set email alerts
|

First trimester medication abortion practice in the United States and Canada

Abstract: We conducted a cross-sectional survey of abortion facilities from professional networks in the United States (US, n = 703) and Canada (n = 94) to estimate the prevalence of medication abortion practices in these settings and to look at regional differences. Administrators responded to questions on gestational limits, while up to five clinicians per facility reported on 2012 medication abortion practice. At the time of fielding, mifepristone was not approved in Canada. 383 (54.5%) US and 78 (83.0%) Canadian fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 23 publications
1
16
0
Order By: Relevance
“…Nationally, 40% of clinics reported that APCs provided at least some abortions. APCs were involved in abortion care in approximately two-thirds of clinics in supportive states, compared with 3% in hostile ones, and this pattern corresponds with a recent study finding that APC provision of medication abortion was substantially higher in the Eastern and Western United States than in the South and Midwest ( Jones et al, 2017 ). These patterns are likely a direct consequence of abortion restrictions combined with the impact of state practice regulations.…”
Section: Discussionsupporting
confidence: 84%
“…Nationally, 40% of clinics reported that APCs provided at least some abortions. APCs were involved in abortion care in approximately two-thirds of clinics in supportive states, compared with 3% in hostile ones, and this pattern corresponds with a recent study finding that APC provision of medication abortion was substantially higher in the Eastern and Western United States than in the South and Midwest ( Jones et al, 2017 ). These patterns are likely a direct consequence of abortion restrictions combined with the impact of state practice regulations.…”
Section: Discussionsupporting
confidence: 84%
“…For example, in the USA, mifepristone may be dispensed only by the prescriber and not by a pharmacist. Ten years after the introduction of mifepristone in the USA, first-trimester medical abortions only represented 36% of all abortions compared to over 80% of first-trimester abortions in many European countries [10,18]. Furthermore, in Australia, where pharmacists may dispense mifepristone, women must pay $560 AUD upfront and attend a mandatory follow-up visit 1 week later [17], and abortion remains legally restricted or prohibited in some jurisdictions [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Medical management (procedure that institute drugs) is the preferred method of dealing with emergency abortions as studies suggest [6][7][8]. It was reported that medication based abortion reduces the occurrence of complications.…”
Section: Introductionmentioning
confidence: 99%
“…The drugs can be self-administered with a maximal success rate as compared to manual aspirations [8][9][10]. In the US alone, medication abortion using mifepristone and misoprostol is practiced by 92% of the providers [6]. Similarly, about 75% of the providers in Canada and 98% of the providers in the US offered medication abortion to people less than 18 years of age [6].…”
Section: Introductionmentioning
confidence: 99%